Modeling of Oxidized PTH (oxPTH) and Non-oxidized PTH (n-oxPTH) Receptor Binding and Relationship of Oxidized to Non-Oxidized PTH in Children with Chronic Renal Failure, Adult Patients on Hemodialysis and Kidney Transplant Recipients - Berthold Hocher; Dominik Oberthür; Torsten Slowinski; Uwe Querfeld; Franz Schaefer; Anke Doyon; Martin Tepel; Heinz J. Roth; Hans J. Grön; Christoph Reichetzeder; Christian Betzel; Franz P. Armbruster (Karger Publishers, 2013)
Background: The biological properties of oxidized and non-oxidized PTH are substantially different. Oxidized PTH (oxPTH) loses its PTH receptor-stimulating properties, whereas non-oxidized PTH (n-oxPTH) is a full agonist of the receptor. This was described in more than 20 well published studies in the 1970s and 80s. However, PTH oxidation has been ignored during the development of PTH assays for clinical use so far. Even the nowadays used third generation assay systems do not consider oxidation of PTH We recently developed an assay to differentiate between oxPTH and n-oxPTH. In the current study we established normal values for this assay system. Furthermore, we compare the ratio of oxPTH to n-oxPTH in different population with chronic renal failure: 620 children with renal failure stage 2-4 of the 4C study, 342 adult patients on dialysis, and 602 kidney transplant recipients. In addition, we performed modeling of the interaction of either oxPTH or n-oxPTH with the PTH receptor using biophysical structure approaches. Results: The children had the highest mean as well as maximum n-oxPTH concentrations as compared to adult patients (both patients on dialysis as well as kidney transplant recipients). The relationship between oxPTH and n-oxPTH of individual patients varied substantially in all three populations with renal impairment. The analysis of n-oxPTH in 89 healthy control subjects revealed that n-oxPTH concentrations in patient with renal failure were higher as compared to healthy adult controls (2.25-fold in children with renal failure, 1.53-fold in adult patients on dialysis, and 1.56-fold in kidney transplant recipients, respectively). Computer assisted biophysical structure modeling demonstrated, however, minor sterical- and/or electrostatic changes in oxPTH and n-oxPTH. This indicated that PTH oxidation may induce refolding of PTH and hence alters PTH-PTH receptor interaction via oxidation induced three-dimensional structure alteration of PTH. Conclusion: A huge proportion of circulating PTH measured by current state-of-the-art assay systems is oxidized and thus not biologically active. The relationship between oxPTH and n-oxPTH of individual patients varied substantially. Non-oxidized PTH concentrations are 1.5 - 2.25 fold higher in patients with renal failure as compared to health controls. Measurements of n-oxPTH may reflect the hormone status more precise. The iPTH measures describes most likely oxidative stress in patients with renal failure rather than the PTH hormone status. This, however, needs to be demonstrated in further clinical studies.